The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3126/ajms.v12i9.37384
|View full text |Cite
|
Sign up to set email alerts
|

I-Gel and LMA classic in the hands of novice: A comparative study

Abstract: Background: Supraglottic airway devices (SADs) such as LMA classic (cLMA), I-Gel, etc. are indispensable tool for the anaesthesiologists experienced in airway management. But studies evaluating the performance of these devices in the hands of unskilled personnel are scarce. Aims and Objective: To determine the procedure time and the proportion of patients having successful placement of I-gel and LMA classic by first-year Post Graduate Trainees (PGTs) of Anaesthesiology who tried insertion of those devices afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…14 in 2020 conducted a study on clinical performance of classic LMA and I-Gel and concluded that both the devices are safe and good in performance with respect to ease of insertion in non-paralyzed anaesthetized adult. In a recent (2021) study, Bhattacharjee et al, 15 observed that I-Gel is a better alternative to LMA Classic in the hands of novice residents for securing the airway in terms of shorter procedure time as well as higher success rate in the first attempt.…”
Section: Discussionmentioning
confidence: 99%
“…14 in 2020 conducted a study on clinical performance of classic LMA and I-Gel and concluded that both the devices are safe and good in performance with respect to ease of insertion in non-paralyzed anaesthetized adult. In a recent (2021) study, Bhattacharjee et al, 15 observed that I-Gel is a better alternative to LMA Classic in the hands of novice residents for securing the airway in terms of shorter procedure time as well as higher success rate in the first attempt.…”
Section: Discussionmentioning
confidence: 99%